STRATEGI HAKIM DALAM MENGATASI KEGAGALAN MEDIASI PADA PERKARA PERCERAIAN: STUDI PADA PA AMBARAWA KELAS I.B - Rudi Nuradi (LPPM STAI Muhammadiyah Probolinggo, 2026)
Dissolution of marriage due to divorce can occur due to talaq or based on a divorce lawsuit (divorce lawsuit). Divorce can only be carried out before a Religious Court hearing, after the Religious Court has attempted and failed to reconcile the two parties. This research is a field research, namely a method to obtain the perceptions, arguments and opinions of the research object. This research also uses an empirical juridical approach research that intends to investigate the application of law to individuals, groups, communities and legal institutions. The primary data source in this research is the Judge of the Ambarawa Religious Court, the secondary data source is data sources from 3 Judges of the Ambarawa Religious Court and PERMA No. 1 of 2016. The results of this study are the judge's strategy in finding solutions to the failure of mediation in divorce cases in the Ambarawa Religious Court. That the main factors behind the failure of mediation in divorce cases are caused by two main factors, namely internal factors and external factors. Of course, with these two main factors will increase the number of divorces that occur in the Ambarawa Religious Court every month, but the mediator continues to strive for peace for the parties with various strategies. It should be noted that the Court itself has prepared and provided space for conflicting parties to resolve their conflicts without going through the judicial process, namely through mediation